2018
DOI: 10.1080/08869634.2017.1420440
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of facial soft tissue values and cranial skeletal widths in different body mass index percentile adolescent subjects

Abstract: Objective The purpose of this study was to analyze facial soft tissue thickness and cranial skeletal transverse widths in adolescent subjects with different body mass index (BMI) percentiles. Methods The 80 subjects were divided into three groups according to BMI percentile: normal-weight, overweight, and obese adolescent subjects. Facial soft tissue linear and cranial skeletal transversal width measurements were performed on lateral and postero-anterior cephalometric radiographs. Results Glabella, nasion, pog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…In a cephalometric study conducted by Buyuk et al (2019), overweight subjects showed larger inter-orbital, maxillary, and nasal cavity width. On the other hand, obese subjects showed larger mastoid mandibular, antegonial, and cranial width.…”
Section: Discussionmentioning
confidence: 94%
“…In a cephalometric study conducted by Buyuk et al (2019), overweight subjects showed larger inter-orbital, maxillary, and nasal cavity width. On the other hand, obese subjects showed larger mastoid mandibular, antegonial, and cranial width.…”
Section: Discussionmentioning
confidence: 94%
“…In addition to this, the mandibular region and the cheek region were the areas affected most by BMI, and the major factor affecting soft-tissue thickness is BMI. In their study on adolescents, Buyuk et al [12] stated that the glabella, pogonion, and gnathion soft-tissue thicknesses were higher in obese and overweight individuals than normally weighted individuals, while the nasion thickness was higher in overweight individuals than normally weighted ones.…”
Section: Discussionmentioning
confidence: 99%
“…BMI is one of the main factors of interpersonal differences in soft-tissue thicknesses. [12] Various imaging methods have been reported for the measurement of facial soft-tissue thickness in living beings. ese are the lateral cephalometric radiography, computerized tomography (CT), ultrasonography, and magnetic resonance imaging (MRI) methods.…”
Section: Introductionmentioning
confidence: 99%
“…(3) previous adenotonsillectomy; (4) absence of clinically noticeable craniofacial syndromes; (5) absence of obesity (BMI ≤ 95 percentile). 11 A validated questionnaire (PSQ) was used for screening patients with suspected OSA. The parents of the selected children filled out this questionnaire regarding nocturnal and daytime potential obstructive sleep breathing signs and symptoms.…”
Section: Methodsmentioning
confidence: 99%